Life Skills-Based Curriculum Innovation Management in Developing Independent Character at MAS Darul Hikmah Purwakarta and MAN 1 Bandung - Andi Saefulloh Anwar; Uus Ruswandi; Ulfiah Ulfiah; Bambang Samsul Arifin (Yayasan Azka Hafidz Maulana, 2026)
This research is motivated by the urgency of strengthening students' independent character amidst the challenges of globalization, technological disruption, and social complexity which demand adaptive competencies and life skills (life skills) which is integral.The purpose of this study is to analyze the planning, implementation, evaluation, as well as supporting and inhibiting factors in the management of life skills-based curriculum innovation in developing students' independent character.This research employed a qualitative approach with a multi-site study method. Data collection techniques included in-depth interviews, participant observation, and documentation studies. Data analysis employed an interactive model that encompassed data reduction, data presentation, and continuous conclusion drawing.The results of the study show that the management of life skills-based curriculum innovation in both madrasas was implemented systematically through participatory planning, strengthening institutional vision, and integration.life skills in subjects, as well as character building through madrasah culture. The implementation of these innovations has had a significant impact on the development of students' independent character, characterized by increased personal responsibility, learning independence, decision-making skills, and readiness to face social challenges. An effective management model is supported by transformational leadership, stakeholder collaboration, and continuous evaluation.